Analisis Nilai Tambah Agroindustri Kopi Bubuk Organik Di Desa Gunung Terang Kecamatan Way Tenong Kabupaten Lampung Barat - Faizal Daud (Jurnal Bakti Agribisnis, 2019)
The objectives of this study were to: 1) calculate the cost, revenue and income of the organic ground coffee agro-industry in Gunung Terang Village, Way Tenong District, West Lampung Regency, 2) calculate the added value obtained from the processing of organic ground coffee agro-industry in Gunung Terang Village, District Way Tenong, West Lampung Regency, 3) to analyze the financial feasibility of the organic ground coffee agro-industry in Gunung Terang Village, Way Tenong District, West Lampung Regency. The results showed that the total production cost of the organic ground coffee agro-industry in Gunung Terang Village, Way Tenong District, West Lampung Regency in one production process was Rp. 3,675,191, the average income was Rp. 4,550,000, the income received was Rp. 879,809. The R / C ratio value is 1.24 indicating that the organic ground coffee agro-industry is profitable. The added value of the organic ground coffee processing agro-industry in Gunung Terang Village, Way Tenong District, West Lampung Regency is IDR 27,459 / Kg. This shows that every sale of 1 kg of organic ground coffee will provide an added value of Rp. 27,459. The organic ground coffee agro-industry in Gunung Terang Village, Way Tenong District, West Lampung Regency is financially feasible to be developed, this can be seen from the calculation of the NPV value of IDR 631,745,317, the IRR value is 31.17% and the Net B value. / C of 3.64.